Retinal Function in Patients with Adalimumab Treatment: Long-term Follow-up with Microperimetry. (17th February 2021) - Szepessy, Zsuzsanna; Barboni, Mirella T. S.; Farkas, Alexandra; Nagy, Zoltán Zsolt; Németh, János
ABSTRACT: Purpose : To examine the effects of a biological treatment (adalimumab) on visual function in patients with ankylosing spondylitis and in uveitic patients without macular edema during one-year treatment with adalimumab. Methods : Sixteen eyes of eight consecutive Caucasian patients treated with adalimumab were followed up using microperimetry (MAIA; CenterVue, Padova, Italy). Five patients had ankylosing spondylitis without uveitis, three patients had panuveitis without macular edema. Macular sensitivity and macular integrity were recorded. Results : During six-month follow-up, the average threshold did not change significantly ( p = .649). Macular integrity was stable ( p = .225). The macular sensitivity point analysis showed no significant effects (examination F(3, 56) = 0.494 and p = .688; point*examination F(108, 2016) = 0.688 and p = .994) during the follow-up. Conclusions : During one-year follow-up, adalimumab did not affect macular function, unlike the well-established maculopathy induced by hydroxychloroquine. Microperimetry may be considered when following-up macular function in patients undertaking adalimumab.